DIASPORA DAN PEMBENTUKAN IDENTITAS ETNIS ARAB DI KOTA MANADO - Muhammad Nur Ichsan Azis (Balai Pelestarian Nilai Budaya Kalimantan Barat, 2020)
This paper describes the Arab people in Manado, as ethnic groups, traders and influentialpeople in the late 19th century to the early 20th century. The Arabs were classified aspeople who are active in trading activities, especially in the shift of commodities, until themid-20th century. They were one of the ethnic groups that play several important roles inthe structure of Indonesian society, including in Manado. These activities influenced theprocess of population movement, diaspora, identity formation, and the axis of commercialnetworks towards the beginning of the 20th century. Manado was a strategic area thatconnected several major and small cities for Arab traders. This paper used historical methodsto examine Arab communities that still survive today. The diaspora of the Arabs to Manadostrengthen the Arabs in Indonesian archipelago. The network that was formed had animpact on the religious identity attached to the Arabs in Manado towards the early 20thcentury AD. One of factors driving the power of the Arabs was the economy which can takeadvantage of the space among other business actors. As a result, they became a new forcein the early 20th century that they were able to attract local people’s attention to stayconnected.